Molecular Phylogeography and Ecological Niche Modeling of Sibbaldia procumbens s.l. (Rosaceae) - Zhang, Hua-Jie; Feng, Tao; Landis, Jacob B.; Deng, Tao; Zhang, Xu; Meng, Ai-Ping; Sun, Hang; Wang, Heng-Chang; Sun, Yan-Xia (Frontiers in Genetics, 2019)
The phylogeographical analysis and ecological niche modeling of the widely distributed Northern Hemisphere Sibbaldia procumbens s.l. can help evaluate how tectonic motion and climate change helped shape the current distribution patterns of this species. Three chloroplast regions (the atpI-atpH and trnL-trnF intergenic spacers and the trnL intron) were obtained from 332 (156 from present study + 176 from the previous study) individuals of S. procumbens s.l. An unrooted haplotype network was constructed using the software NETWORK, while BEAST was used to estimate the divergence times among haplotypes. Ecological niche modeling was performed by MAXENT to explore the historical dynamic distribution of S. procumbens s.l. The haplotype distribution demonstrates significant phylogeographical structure (NST > GST; P<0.01). The best partitioning of genetic diversity by SAMOVA produced three groups, while the time to the most recent common ancestor of all haplotypes was estimated to originate during the Miocene, with most of the haplotype diversity having occurred during the Quaternary. The MAXENT analysis showed S. procumbens. s.l. had a wider distribution range during the last glacial maximum (LGM) and a narrower distribution range during the last interglacial (LIG), with predictions into the future showing the distribution range of S. procumbens. s.l. shrinking.